Aspergillus spp. and azole-resistance characterization on mechanic protection gloves from waste sorting industry - Viegas, Carla (2022)
Project "Waste Workers’ Exposure to Bioburden through Filtering Respiratory Protective Devices” (IPL/2018/WasteFRPD_ESTeSL).